Pulse intensity characterization of the LCLS nanosecond double‐bunch mode of operation. (30th March 2018) - Sun, Yanwen; Decker, Franz-Josef; Turner, James; Song, Sanghoon; Robert, Aymeric; Zhu, Diling
Abstract : Details and performances of a transmissive pulse intensity diagnostic for the LCLS `nanosecond double‐bunch' mode are presented. Abstract : The recent demonstration of the `nanosecond double‐bunch' operation mode, i.e. two X‐ray pulses separated in time between 0.35 and hundreds of nanoseconds and by increments of 0.35 ns, offers new opportunities to investigate ultrafast dynamics in diverse systems of interest. However, in order to reach its full potential, this mode of operation requires the precise characterization of the intensity of each X‐ray pulse within each pulse pair for any time separation. Here, a transmissive single‐shot diagnostic that achieves this goal for time separations larger than 0.7 ns with a precision better than 5% is presented. It also provides real‐time monitoring feedback to help tune the accelerator parameters to deliver double pulse intensity distributions optimized for specific experimental goals.